2021
DOI: 10.1016/j.cjtee.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

PTSD: Past, present and future implications for China

Abstract: There has been a long history since human beings began to realize the existence of post-traumatic symptoms. Posttraumatic stress disorder (PTSD), a diagnostic category adopted in 1980 in the Diagnostic and Statistical Manual of Mental Disorders-Ⅲ, described typical clusters of psychiatric symptoms occurring after traumatic events. Abundant researches have helped deepen the understanding of PTSD in terms of epidemiological features, biological mechanisms, and treatment options. The prevalence of PTSD in general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 214 publications
(269 reference statements)
0
20
0
3
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic is a traumatic event. 1 People who experienced such an event are liable for post-traumatic stress disorders and harmful psychiatric illness. 2–8 One systematic review and meta-analysis found an increase in mental health problems such as depression, anxiety, distress, and insomnia during the COVID-19 pandemic, and the prevalence of these symptoms was 31.4%, 31.9%, 41.1%, and 37.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic is a traumatic event. 1 People who experienced such an event are liable for post-traumatic stress disorders and harmful psychiatric illness. 2–8 One systematic review and meta-analysis found an increase in mental health problems such as depression, anxiety, distress, and insomnia during the COVID-19 pandemic, and the prevalence of these symptoms was 31.4%, 31.9%, 41.1%, and 37.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The core symptoms of PTSD are intrusiveness of the traumatic event, avoidance of trauma-related stimuli, negative changes in cognition and emotion, and hypervigilance and overreaction. 7 The 12-month prevalence of PTSD ranges from 0.2% to 3.8%, according to different social backgrounds and countries of residence. 8 The lifetime prevalence of PTSD was estimated as 6.4% in a nationwide investigation in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…10 After exposure to a major earthquake, there was a lack of decline in the prevalence rate of significant PTSD symptoms. 7 The severity of PTSD correlates with other psychological and physical disorders, eg, over half of PTSD patients suffer from substance use disorders, and higher PTSD severity is related to poorer sleep status, 9,11 ultimately leading to a reduced quality of life. 12 In addition, PTSD can impair work performance in fields demanding a higher level of cognitive function, including decision making, attentional ability, and executive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a complex and debilitating illness triggered by terrifying events, which is often companied by cognitive impairment, chronic pain, and affective disorders (Compean and Hamner 2019). The prevalence of PTSD in the general population is estimated at approximately 7% and higher among people experienced major traumatic events before (Zhou et al 2021). For example, coronavirus disease 2019 (COVID-19) is a major source of traumatic stress for people around the globe since 2019.…”
Section: Introductionmentioning
confidence: 99%